Claiming management actions according to the archaeological excellence of the Port of Sanitja - Fernando Contreras Rodrigo (Culturas, 2021)
The cultural entity Sanisera, in accordance with its line of action, concentrated in the port of Sanitja (Menorca, Balearic Islands) with regard to heritage management activities and archaeological research, claiming the value of the Sanitja archaeological site to attract attention of different organizations and appropriate mechanisms are established that serve to propose plans that maintain the heritage value of its archaeological complex and preventive protection measures in the most unique heritage area in the north of Menorca.